Inventory of Stingless Bees in Customary Forest of Imbo Putui, Kampar Regency, Indonesia - Marsya, Yana Yunisa; Gesriantuti, Novia; Badrun, Yeeri; Syarif, Nuskan; Tas’ad, Said Faizan (Photon: Jurnal Sain dan Kesehatan, 2025)
Information on stingless bee diversity in customary forest of Imbo Putui is still lacking so there is no data of stingless bees in the forest.  The purpose of this study was to identify the species of stingless bees found in Imbo Putui customary forest. The search for stinglees bee nests was carried out using exploration method in three predetermined areas. The area was roadside (Zone I), inside the forest (Zone II), and around the river and oil palm plantation (Zone III). Data analysis was carried out quantitative descriptive. The result of the study found 7 species of stingless bees, 4 species of which with majority conservation status were found, namely Heterotrigona itama, Tetragonula laeviceps (yellow, black), Tetragonula drescheri and Tetragonilla collina. Meanwhile minority species found are Tetragonula iridepennis, Homotrigona fimbriata and Tetragonula testaceitarsis. Base on presence of 3 species that are classified as minorities found,  it can be conclude that the ecosystem of Imbo Putui customary forest is  still maintained and has not experienced significant changes.